(untitled) (Genius Repository, 2023)
The text discusses the introduction of corbels or brackets, which are structural features that extend from a wall or column to support a weight. Corbels are commonly used in precast buildings to support prefabricated beams on columns. They are different from deep beams and are considered as mechanisms of shear transfer. Traditional design approaches involve using horizontal stirrups to enhance the shear capacity of corbels and prevent failure. The text mentions various researchers who have studied the behavior and strength of reinforced concrete corbels. Franz and Niedenhoff presented a truss analogy for corbel construction. Kriz and Raths conducted tests on corbels with different variables such as breadth, effective depth, reinforcing ratio, and concrete strength. They found that the strength of corbels is directly related to the strength of the concrete and the primary reinforcement ratio. The text also discusses the Mast shearfriction theory, which is based on the concept of frictional resistance along cracks in concrete. The theory considers the reinforcement that spans a crack to provide frictional resistance and undergo yielding due to strain. Hermansen and Cowan proposed a modified shear-friction theory that includes the coefficient of friction and apparent cohesive stresses. Overall, the text provides an overview of corbels, their behavior, and different theories and approaches related to their design and strength.